2012
DOI: 10.1016/j.vetpar.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Association between contamination of public squares and seropositivity for Toxocara spp. in children

Abstract: A concomitant study was carried out, of the association of positive serology for Toxocara spp. in 90 children who played in public squares used for leisure, with the frequency with which each child used these areas, and the presence of eggs of Toxocara spp. in the sand or grass in these locations. The sand and grass of their peridomiciles and school playgrounds, as well as the feces of their dogs were also analyzed for Toxocara. Serum samples were tested for IgG antibodies to Toxocara canis excreted-secreted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 24 publications
2
54
0
4
Order By: Relevance
“…10,27,[30][31][32]36,40 In all of these studies, a higher proportion of patients with asthma was found among those infected with Toxocara, which lends this infection greater relevance in terms of public health.…”
Section: Resultsmentioning
confidence: 93%
“…10,27,[30][31][32]36,40 In all of these studies, a higher proportion of patients with asthma was found among those infected with Toxocara, which lends this infection greater relevance in terms of public health.…”
Section: Resultsmentioning
confidence: 93%
“…Studies have concentrated on assessing egg contamination of playgrounds, parks, sandpits, and backyards/gardens and have shown contamination to be prevalent [47]. Although such areas seem to provide opportunities for infection, the role of different domestic and wild defi nitive hosts in the contamination of these areas is unclear (McPherson, 2013).…”
Section: Soil Contamination Of Toxocara Spp Eggs Survival and Dispermentioning
confidence: 99%
“…O simples hábito de lavar as mãos diminui as chances de se contaminar e foi estatisticamente associado ao decréscimo da prevalência (34). A correta vermifugação de cães e gatos, tanto filhotes quanto animais adultos é de extrema importân-cia, pois a presença de animais não parasitados contribui significativamente para a soronegatividade em crianças (14). A vermifugação de filhotes deve ocorrer com dois, quatro, seis e oito semanas de idade, e depois mensalmente até os seis meses; sendo que em gatos ela pode começar com três semanas (66).…”
Section: Parâmetrounclassified
“…Estudos demonstraram altas taxas de contaminação em ambientes públicos, como praças e parques, com ovos provenientes das fezes de cães parasitados (13)(14)(15)(16)(17), o que faz com que essa doença seja de grande importân-cia para a saúde pública.…”
Section: Introductionunclassified